2021
DOI: 10.1001/jamaophthalmol.2020.5044
|View full text |Cite|
|
Sign up to set email alerts
|

Insights From Survival Analyses During 12 Years of Anti–Vascular Endothelial Growth Factor Therapy for Neovascular Age-Related Macular Degeneration

Abstract: IMPORTANCEAlthough multiple imputation models for missing data and the use of mixed-effects models generally provide better outcome estimates than using only observed data or last observation carried forward in clinical trials, such approaches usually cannot be applied to visual outcomes from retrospective analyses of clinical practice settings, also called real-world outcomes.OBJECTIVE To explore the potential usefulness of survival analysis techniques for retrospective clinical practice visual outcomes. DESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…In real world studies, the relationship between age and visual outcome is not as consistent ( Table 2 ). Though associations are found in larger observational cohorts, 28 , 29 , 50 suggesting this is due to smaller sample sizes and larger patient variations in combination with its relatively small effect size.…”
Section: Patient Characteristicsmentioning
confidence: 93%
See 3 more Smart Citations
“…In real world studies, the relationship between age and visual outcome is not as consistent ( Table 2 ). Though associations are found in larger observational cohorts, 28 , 29 , 50 suggesting this is due to smaller sample sizes and larger patient variations in combination with its relatively small effect size.…”
Section: Patient Characteristicsmentioning
confidence: 93%
“…In real world studies, the relationship between age and visual outcome is not as consistent (Table 2). Though associations are found in larger observational cohorts, 28,29,50 suggesting this is due to smaller sample sizes and larger patient variations in combination with its relatively small effect size. The effect of age may be influenced by other factors, with Yamashiro et al 51 finding that age was associated with 12-month VA changes in typical nAMD patients, but not for those presenting with the polypoidal choroidal vasculopathy (PCV) variant of AMD.…”
Section: Patient Characteristics Agementioning
confidence: 94%
See 2 more Smart Citations
“…A 12-year clinical cohort study on the patients with Ranibizumab and Aflibercept concluded that the visual outcomes positive within the first 2.0 years after treatment. However, within 8.7 years the visual outcome downgraded to poor vision [ 78 ].…”
Section: Advanced Therapeutics and Delivery Strategies For Namdmentioning
confidence: 99%